Thoughts. Occasioned by the perusal of Dr. Parr's spital sermon, preached at Christ Church, April 15, 1800: being a reply to the attacks of Dr. Parr, Mr. Mackintosh [...] (Scholars' Facsimiles & Reprints, 1968)
Photomechanical reprint of the ed.: London, Taylor and Wilks, 1801. In: W. Godwin, Uncollected writings (1785-1822).